Neonatal bloodstream infections in a Ghanaian Tertiary Hospital: Are the current antibiotic recommendations adequate?. Issue 1 (December 2016) - Labi, Appiah-Korang; Obeng-Nkrumah, Noah; Bjerrum, Stephanie; Enweronu-Laryea, Christabel; Newman, Mercy
Abstract Background Diagnosis of bloodstream infections (BSI) in neonates is usually difficult due to minimal symptoms at presentation; thus early empirical therapy guided by local antibiotic susceptibility profile is necessary to improve therapeutic outcomes. Methods A review of neonatal blood cultures submitted to the microbiology department of the Korle-Bu Teaching Hospital was conducted from January 2010 through December 2013. We assessed the prevalence of bacteria and fungi involved in BSI and the susceptibility coverage of recommended empiric antibiotics by Ghana Standard Treatment guidelines and the WHO recommendations for managing neonatal sepsis. The national and WHO treatment guidelines recommend either ampicillin plus gentamicin or ampicillin plus cefotaxime for empiric treatment of neonatal BSI. The WHO recommendations also include cloxacillin plus gentamicin. We described the resistance profile over a 28-day neonatal period using multivariable logistic regression analysis with linear or restricted cubic splines. Results A total of 8, 025 neonatal blood culture reports were reviewed over the four-year period. Total blood culture positivity was 21.9 %. Gram positive organisms accounted for most positive cultures, with coagulase negative staphylococci (CoNS) being the most frequently isolated pathogen in early onset infections (EOS) (59.1 %) and late onset infections (LOS) (52.8 %). Susceptibility coverage of early onset bacterial isolates were 20.7 % to ampicillin plus cefotaxime, 32.2 % to the combination of ampicillin and gentamicin, and 71.7 % to cloxacillin plus gentamicin. For LOS, coverage was 24.6 % to ampicillin plus cefotaxime, 36.2 % to the combination ampicillin and gentamicin and 63.6 % to cloxacillin plus gentamicin. Cloxacillin plus gentamicin remained the most active regimen for EOS and LOS after exclusion of BSI caused by CoNS. For this regimen, the adjusted odds of resistance decreased between 12-34 % per day from birth to day 3 followed by the slowest rate of resistance increase, compared to the other antibiotic regimen, thereafter until day 28. The trend in resistance remained generally unchanged after excluding data from CoNS. Multidrug resistant isolates were significantly (p -value <0.001) higher in LOS (62.4 %, n = 555/886) than in EOS (37.3 %, n = 331/886). Conclusions There is low antibiotic susceptibility coverage for organisms causing neonatal bloodstream infections in Korle-Bu Teaching Hospital when the current national and WHO recommended empiric antibiotics were assessed. A continuous surveillance of neonatal BSI is required to guide hospital and national antibiotic treatment guidelines for neonatal sepsis.